An introduction to cultural transduction (2017)
A few years back, while we were studying a variety of cases where media products had been changed or altered to suit specific markets, we discovered that there was a great amount of literature on the topic. The various authors we encountered talked about many different aspects of the process and provided a vocabulary that was developed to answer the particular concerns they had found when addressing their specific subject. However, as we pierced through pages of books and articles, we discovered that many of the terms were different, but the general meanings they were giving them were similar. Moreover, many of the terms and concepts proposed by the various authors seemed complementary and, in our eyes, the articulation of said concepts, bringing them together, provided a more nuanced and comprehensive picture of the subject. That is how we decided to create a general framework that could encompass all of the terminology and theoretical perspectives that had been developed, in order to provide a common ground for analysis of the processes of modification of cultural products as they crossed borders and markets.